2021
DOI: 10.3390/su132313361
|View full text |Cite
|
Sign up to set email alerts
|

Why Do We Harm the Environment or Our Personal Health despite Better Knowledge? The Knowledge Action Gap in Healthy and Climate-Friendly Behavior

Abstract: Non-communicable diseases, such as hypertension, diabetes, or depression, result from an interplay of physiological, genetic, behavioral, and environmental aspects. Together with climate change, they are arguably among the most significant challenges mankind faces in the 21st century. Additionally, the bidirectional influences of climate change and health on each other are undisputed. Behavioral changes could curb both climate change and the spread of non-communicable diseases. Much effort has been put into in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…However, the relationship between cognitive, affective and behavioural aspects remains a controversy. Although early models of environmental behaviour claim a linear correlation between knowledge, attitude and behaviour [82], many recent studies disagree with these findings, e.g., [52]. Instead, the relationship can be characterised as very complex, not at all mono-directional, and certainly influenced by many additional factors, such as feedback, social norms, economic situation, values, and beliefs [83][84][85][86][87][88][89].…”
Section: Discussion Of Results Of Self-reporting Online Surveys About...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the relationship between cognitive, affective and behavioural aspects remains a controversy. Although early models of environmental behaviour claim a linear correlation between knowledge, attitude and behaviour [82], many recent studies disagree with these findings, e.g., [52]. Instead, the relationship can be characterised as very complex, not at all mono-directional, and certainly influenced by many additional factors, such as feedback, social norms, economic situation, values, and beliefs [83][84][85][86][87][88][89].…”
Section: Discussion Of Results Of Self-reporting Online Surveys About...mentioning
confidence: 99%
“…Although there are many controversies about the correlation between the attributes, many authors (e.g., [95]) found that the correlations between affective and behavioural subscales are significantly higher than those between cognitive and affective as well as cognitive and behavioural [52]. Therefore, high achievements in the affective attributes increase the probability that the students will change their behaviour, and it indicates that they might possess a general understanding and acceptance for measures tackling climate change (e.g., legal regulations).…”
Section: Discussion Of Results Of Self-reporting Online Surveys About...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, research on certain NCDs, such as mental health disorders and their relation to climate change, is limited and requires more attention. The study by Frick et al, 2021, discusses the knowledge-action gap in healthy and climate-friendly behavior, indicating a need for more research on behavior change to mitigate both climate change and the spread of NCDs [43].…”
Section: Future Research and Directionsmentioning
confidence: 99%
“…Firstly, it establishes trust with the audience by providing comprehensive and well-researched information, hence related to the element of credibility [34]. Secondly, informativeness educates the audience, which is often a prerequisite for bridging the knowledge-action gap [35,36]. For example, in water conservation campaign communications, informativeness plays a vital role in educating the public about water-related issues and promoting sustainable behaviour [17,37,38].…”
Section: Informativenessmentioning
confidence: 99%